COMPARISON OF MORPHOLOGICAL CHARACTERISTICS AND SPECIFIC MOTOR OF JUNIOR SOCCER PLAYERS IN TWO PERIODS - Sami Sermaxhaj; Abedin Bahtiri; Fitim Arifi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The purpose of this paper is to compare the number of of morphological cha¬ra¬cte¬ristics and specific motor between players Junior (U-19) in two time periods in 2004 and 2014. The research was conducted on a sample of 100 young soccer players (U-19 Lea¬gue first Kosovo) divided into two groups: The first group comprised of 50 players U-19 to the five best clubs in 2003/04 season and the second group of 50 players U-19 also five best clubs 2013/14 season. In the two generations of players were conducted measurements of morphological characteristics and specific motor. To validate the differences between U-19 players two generations is used the method T-Test. The results obtained have shown statistically significant differences in favor of players U19 2013/14 generation to generation U-19 2003/04 in two storage areas (anthropometric and specific motor) ..These changes are in favor of players U-19 2014 generation to generation in 2004 hypothetically can justify as a result of vocational education framework coaches and completion of program content with additional exercises fitness to young soccer players.